Peroneus Brevis Muscle Flap as a Tissue Cover - Vaghani , Sanjay Gordhanbhai; Chaudhari , Ganesh Sadashiv (Current Innovations in Medicine and Medical Science Vol. 8, 2022)
In this case series, authors have shared their experience with peroneus brevis muscle flaps, proximally or distally based to cover defects from lower mid leg to ankle region. Reconstruction of the distal third of the leg is associated with the highest complication rate for local procedures because of the paucity of reliable local flaps, which is because of the limited amount of available local tissue. The mid-leg and ankle region is more prone to full-thickness soft tissue loss after trauma. Due to its placement in the subcutaneous plane and the shin region's unstable blood supply, implants utilised in osteosynthesis in this area are also susceptible to exposure. For the reconstruction of minor to medium-sized defects in this region, various approaches, such as local flap to free flap, are outlined. Literature also provides a good description of the peroneus brevis. In this case series which was done over the period of six years that includes 10 patients with post-traumatic as well as post orthopaedics surgical intervention defects in lower mid leg and ankle region. Patients were selected for proximally and distally based peroneus brevis muscle flap according to the location of defects. Data regarding age, sex, aetiological factor, size of defect, type of flap, survival of flap, donor site complications were recorded. Out of 10 patients, eight were males and two were females. Major aetiological factor was two wheeler road traffic accident. Majority of the patient had orthopaedic surgical intervention for fracture fixation prior to or along with flap surgery. A excellent, dependable, and relatively simple solution for minor to medium-sized soft tissue defect in the mid-leg and ankle region is the peroneus brevis muscle. Peroneus brevis muscle flap is highly recommended by authors for small- to medium-sized soft tissue defect.